Caracterização do lipídeo extraído artesanalmente da pele de frango - Vasconcelos, Maria de Fátima Martins (2021)
Chicken is an economically accessible meat product, very commercialized, with numerous by-products within the food area. Its production chain, which ranges from creation to marketing, generates a large amount of waste material, and most of this material can be used in other activities, contributing to the sustainability and maintenance of the ecosystem. As an example, we mention the residues from the production of broiler chicken, one of the main ways of marketing chicken in the world, where chicken skin stands out, which contains in its composition the presence of lipids, important for physiological studies, nutritional and physicochemical and present in some foods. In the literature, some studies report that the lipid profile of chickens and unsaturated fatty acids are in greater quantity, especially when compared to other animal fats, such as beef and pork. Thus, the aim of this study was to carry out the artisanal obtainment of the lipid extracted from the skin of chicken, and characterize it through analysis of acidity, refractive index, moisture, color, verification of the chemical composition through attenuated total reflection spectra in the Fourier transform infrared (ATR-FTIR) and quantification of fatty acid profile by gas chromatography and mass spectrometry. The samples that were used for analysis were separated and named as: OFSC (in natura), OFCC1 (chicken skin frying) and OFCC20 (twenty consecutive cooking processes without adding food), where OFCC20 was used only for the analysis was carried out by gas chromatography. In the OFSC and OFCC1 samples, no significant differences were found in the acidity, refractive index and color results, and the data obtained were within the limits determined in the normative instructions. As for the moisture parameter, the OFSC and OFCC1 samples differed significantly, which may have occurred due to the frying process, reducing its content as a function of water heating and evaporation. The analyzes performed by FTIR resulted in absorption bands that indicated the presence of monounsaturated fatty acids, in the following absorption frequencies it represented the presence of esters, and no absorption band was present referring to lipid oxidation. In gas chromatography analyses, the profile of monounsaturated fatty acids was shown to be in greater quantity compared to saturated acids, especially omega-9, and polyunsaturated, omega-6 and omega-3 were also present. In the total ions for the fatty acid methyl esters, the peaks for the three samples indicated that OFCC1 and OFCC20 did not suffer a decrease in unsaturated ones, while the saturated ones remained stable, not showing degradation due to the frying process. In the Principal Component Analysis (PCA), the samples showed monounsaturated, polyunsaturated and saturated acids. Samples OFCC1 and OFCC20, referring to the successive frying and heating process, demonstrated good oxidative stability due to the absence of changes in their lipid composition, which are recurrent in oils that undergo frying processing. In addition, the presence of omega 9, 6 and 3 in the lipid extracted from chicken skin is one of the main positive points for its consumption.